(untitled) (American Journal of Innovation in Science and Engineering, 2023)
Seafood wastes raise environmental concerns and many studies focus on recycling those wastes into chitosan. However, the environmental impact of that process is underestimated. Indeed, a significant amount of toxic wastes is released, potentially harmful to humans and the environment. This study therefore focuses on reducing of that adverse impact by recycling the waste produced during the first step of the production of chitosan: demineralization. By varying the concentration of the acid while keeping stoichiometric ratios, it was shown that the concentration plays a vital role in the efficiency of the demineralization and the purity of the salts. This effect of the concentration on such reaction is still poorly investigated and this study thus offers a deeper knowledge to the chitosan research. Moreover, it was concluded that calcium salts from the transformation of crab wastes into chitosan can be collected and reused. Nevertheless, studies about recycling waste from the other steps of the chitosan production are needed to reduce this process’s environmental impact even more.